Determination of Iron (Fe), Zinc (Zn) Levels and Organoleptic Tests in Coconut Pulp Flour - Muh. F. Khaykal; Sri H. V. Pulukadang (Jurnal Akademika Kimia, 2021)
Coconut pulp is a by-product of coconut milk which contains high protein and good nutrition. This study aimed to determine the iron (Fe) and zinc (Zn) levels in coconut pulp flour using atomic absorption spectrophotometry and determine the characteristics of coconut pulp flour using organoleptic tests. The results showed that iron (Fe) level was 44.075 mg/kg and zinc (Zn) was 24.2 mg /kg. The organoleptic characteristics of the pulp were white and brownish for the dry powder, coconut-scented, a powder-shaped texture, and normal taste. The highest percentage level of hedonic scale for each criterion was 64% preferred for color, 52% preferred for aroma, 48% preferred for texture, and 52% preferred for taste. Based on these results, coconut pulp can be an alternative local food to meet iron and zinc needs for humans. The processing of coconut pulp as food can be used as a substitute flour in making bread, cakes, cookies, and other food preparations.